Lexical hedges: a study of cultural and disciplinary variation in academic research articles / Sarmad J. Mohammed - J. Mohammed, Sarmad (2011)
There is a widely held belief that academic writing is purely objective, impersonal and informational, designed to disguise the author and deal directly with facts and the search for independent truth. But effective academic writing is like any other type of discourse in that it is interactive; it involves writers trying to influence their reader by persuading them of the correctness of their claims (Hyland, 1998a, p. iii). One important means of achieving this is the use of hedges to present claims with caution, precision, and humility. Hedging is one of the features associated with academic writing. This study examines the distribution of forms and functions of lexical hedges in a corpus of 24 research articles written in English. A total of almost 48,000 words are analyzed from two different disciplines namely biochemistry and applied linguistics, and from two rhetorical sections namely introduction and discussion sections. I also explore how the writers from different cultures employ these means in their academic writing. The results show that the American authors use 14% more hedging forms than Arabic authors in biochemistry discipline and almost 15% in the applied linguistics discipline. On the other hand, the results also reveal that linguists used hedges considerably less than the scientists in both genres. In terms of hedging functions, the results show that American authors employed more hedging function than Arabic authors in both disciplines. The discussion sections of RAs contain more hedging forms and functions than the introduction sections in both disciplines. In the overall incidence of hedging, however, the results indicate that noticeable, disciplinary variation in the use of lexical hedges is found in the RA corpus, hedging becoming more frequent in the field of biochemistry in comparison with the .- field of applied linguistic.